2004
DOI: 10.1111/j.1365-2842.2004.01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strength of microwaveable acrylic resin for denture repair

Abstract: Microwaveable acrylic denture resins are believed to provide an effective means of repairing fractured dentures. This in vitro investigation compared the bond strength of a microwaveable acrylic resin as a denture repair material to two established auto-polymerized resins. Fifty-one specimens were made using Lucitone 199 as a simulated denture base, and were then divided into three groups of 17 samples each. Each test group was bonded with the following acrylic resins: Acron Mc, Rapid Repair and Palapress. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 13 publications
(17 reference statements)
2
25
0
4
Order By: Relevance
“…5,37,38 The advantages of microwave-polymerized acrylic resins are the lower residual monomer content and superior physical properties. 9 Rached and Del Bel Cury 25 found that the transverse strength of microwavepolymerized acrylic resin was 93% to 106% of the original acrylic resin. Studies have shown that when the fractured heat-polymerized specimens are repaired with microwave-polymerized acrylic resin, the transverse strength and impact resistance of the repaired specimens are superior to those of specimens repaired with autopolymerizing acrylic resin.…”
Section: Effect Of Repair Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,37,38 The advantages of microwave-polymerized acrylic resins are the lower residual monomer content and superior physical properties. 9 Rached and Del Bel Cury 25 found that the transverse strength of microwavepolymerized acrylic resin was 93% to 106% of the original acrylic resin. Studies have shown that when the fractured heat-polymerized specimens are repaired with microwave-polymerized acrylic resin, the transverse strength and impact resistance of the repaired specimens are superior to those of specimens repaired with autopolymerizing acrylic resin.…”
Section: Effect Of Repair Materialsmentioning
confidence: 99%
“…The choice of denture base resin and repair material combination may also influence the final strength of denture repair. 3,9,[17][18][19][20][21][22][23][24][25] This article reviews some of the current literature with regard to the most important factors that may influence the strength of acrylic denture repairs.…”
mentioning
confidence: 99%
“…Alternativas semejantes también fueron sugeridas por otros autores que evaluaron la influencia del condicionamiento físico-químico de la superficie en reparaciones de dientes perdidos (11,18,20,23,26).…”
Section: Discussionunclassified
“…La metodología empleada en el presente trabajo fue adaptada de estudios previamente consultados (11,18,20,23). Inicialmente los dientes fueron embutidos individualmente en resina acrílica químicamente activada (Jet, Artigos odontológicos Clássico, SP/Brasil), con la ayuda de tubos de PVC (20mm de diámetro por 20 milímetros de altura).…”
Section: Materiales Y Métodosunclassified
See 1 more Smart Citation